The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

Antarctic krill swarm characteristics in the Southeast Atlantic sector of the Southern Ocean - Krafft, Bjørn A.; Skaret, Georg; Knutsen, Tor; Melle, Webjørn; Klevjer, Thor; Søiland, Henrik (Marine ecology. Progress series, 2012)
Knowledge about swarm dynamics and underlying causes is essential to understand the ecology and distribution of Antarctic krill . We collected acoustic data and key environmental data continuously across extensive gradients in the little-studied Southeast Atlantic sector of the Southern Ocean. A total of 4791 krill swarms with swarm descriptors including swarm height and length, packing density, swimming depth and inter-swarm distance were extracted. Through multivariate statistics, swarms were categorized into 4 groups. Group 2 swarms were largest (median length 108 m and thickness 18 m), whereas swarms in both Groups 1 and 4 were on average small, but differed markedly in depth distribution (median: 52 m for Group 1 vs. 133 m for Group 4). There was a strong spatial autocorrelation in the occurrence of swarms, and an autologistic regression model found no prediction of swarm occurrence from environmental variables for any of the Groups 1, 2 or 4. Probability of occurrence of Group 3 swarms, however, increased with increasing depth and temperature. Group 3 was the most distinctive swarm group with an order of magnitude higher packing density (median: 226 ind. m ) than swarms from any of the other groups and about twice the distance to nearest neighbor swarm (median: 493 m). The majority of the krill were present in Group 3 swarms, and the absence of association with hydrographic or topographic concentrating mechanisms strongly suggests that these swarms aggregate through their own locomotion, possibly associated with migration.
Keywords: Bouvetøya; Sørishavet; datainnsamling; ekkolodd; krill; marin biologi; plankton; økologi